Effectiveness of Submucosal Dexamethasone to Control Postoperative Pain & Swelling in Apicectomy of Maxillary Anterior Teeth - Shah, Shahzad Ali; Khan, Irfanullah; Kanwal, Humer (International Journal of Health Sciences, 2011)
Purpose: The purpose of this study was to evaluate the effect of submucosal dexamethasone injection to control postoperative pain and swelling in apicectomy of maxillary anterior teeth. Methods: A randomized, controlled trial comprising 60 adult patients (68.3% male, 31.7% female) with no local or systemic problems was conducted. Patients were randomly divided into two groups: Group A was given 4mg dexamethasone injection perioperatively. Group B (control group) was treated conventionally without any steroid injection. Postoperative pain and swelling was evaluated using a visual analog scale (VAS). Objective measurements of facial pain and swelling were performed daily up to six days postoperatively. Results: Dexamethasone group showed significant reduction in pain and swelling postoperatively compared with the control. Conclusion: Submucosal dexamethasone 4mg injection is an effective therapeutic strategy for swift and comfortable improvement after surgical procedure and has a significant effect on reducing postoperative pain and swelling. The treatment offers a simple, safe, painless, noninvasive and cost effective therapeutic option for moderate and severe cases. Key Words: Pain control, dexamethasone injection, swelling, apicectomy